IMPACT OF COVID-19 PANDEMIC ON HOTEL FITNESS INSTRUCTORS IN BANGKOKAND QUALITY OF LIFE - Laeieddeenan, Pimthip; Supaporn, Salee; Supaporn, Salee (Journal of Faculty of Physical Education, 2022)
The purpose of this study was to determine (1) the impact and working barriers (2) the quality of life of hotel fitness instructors during the COVID-19 pandemic; and (3) the earnings before and during the pandemic. Twenty fitness instructors, working for 4–5 star hotels in Bangkok, were purposively selected as participants. Data were collected using interview, critical incidence, and stimulated recall. Data were inductively analyzed and established trustworthiness through triangulation. Findings indicated four themes. First, the impact of COVID-19 pandemic included 6 categories; (1.1) inadequate expense; (1.2) reduction in work days; (1.3) shifting to work in other divisions; (1.4) working from home; (1.5) getting fired; and (1.6) irritation of nostrils because of too many Antigen Test Kit/ATK. Second, obstacles to work as fitness instructors involved with five categories, namely: (2.1) difficulty breathing with a mask; (2.2) injured hands due to frequent washing and spraying alcohol; (2.3) increasing fitness cleaning tasks; (2.4) having problems related to social distance; and (2.5) not complying with fitness rules for preventing COVID-19 among users. Third, self-evaluation mean scores related to the impact on quality of life, (from 1-9, lower scores represented a lower impact than those higher scores), was 6.90, indicated the great impact of the COVID-19 pandemic. Forth, the monthly income of participants decreased 47.6% during the COVID-19 pandemic. In conclusion, the COVID-19 pandemic had a negative impact, hindered the jobs of fitness instructors, as well as reduced income and quality of life.